2006
DOI: 10.1021/ja061413o
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin Biosynthesis in Eukaryotes:  Characterization of the Enzyme-Bound Product of Thiazole Synthase from Saccharomyces cerevisiae and Its Implications in Thiazole Biosynthesis

Abstract: The biosynthesis of thiamin pyrophosphate in eukaryotes is different from the prokaryotic biosynthesis and is poorly understood to date. Only one thiazole biosynthetic gene has been identified (Thi4 in Saccharomyces cerevisiae). Here we report the identification and characterization of a Thi4-bound metabolite that consists of the ADP adduct of 5-(2-hydroxyethyl)-4-methylthiazole-2-carboxylic acid. The unexpected structure of this compound yields the first insights into the mechanism of thiamin thiazole biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…The following gradient was used at 1 mL·min −1 flow rate: solvent A is water, solvent B is 100 mM KPi, pH 6.6, solvent C is Methanol; 0 min 100% B; 5 min 10% A and 90% B; 8 min 25% A, 60% B and 15% C; 14 min 25% A, 60% B and 15% C; 19 min 30% A, 40% B and 30% C; 21 min 100% B; 30 min 100% B [14]. The absorbance at 258 nm was monitored.…”
Section: Hplc Analyses Of Ligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following gradient was used at 1 mL·min −1 flow rate: solvent A is water, solvent B is 100 mM KPi, pH 6.6, solvent C is Methanol; 0 min 100% B; 5 min 10% A and 90% B; 8 min 25% A, 60% B and 15% C; 14 min 25% A, 60% B and 15% C; 19 min 30% A, 40% B and 30% C; 21 min 100% B; 30 min 100% B [14]. The absorbance at 258 nm was monitored.…”
Section: Hplc Analyses Of Ligandsmentioning
confidence: 99%
“…Many intermediates of the thiamine pathway are predicted by extrapolations from the characteristics of the prokaryotic thiamine biosynthesis [14]. Labeling studies in S. cerevisiae have demonstrated that the thiamine-thiazole is synthesized from an unidentified five-carbon carbohydrate, glycine, and cysteine [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the reaction catalyzed by the thiazole synthase (THI4) has not yet been fully reconstituted, the enzyme copurified with three tightly bound metabolites (35, 40 and 41) and the structure of the enzyme complexed to 41 has been determined. [12][13][14][15] The identity of these metabolites suggested that NAD is the precursor to the thiazole. This was confirmed by the identification of three partial reactions catalyzed by the C204A mutant of THI4 (28 to 29, 29 to 30 and 29 to 35 in Figure 5).…”
Section: Thiamin Biosynthesis In Saccharomyces Cerevisiaementioning
confidence: 99%